2004
DOI: 10.1073/pnas.0405074101
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of cardiac presynaptic α 2C adrenergic receptors: Diverse intragenic variability with haplotype-specific functional effects

Abstract: The presynaptic ␣2C adrenergic receptors (AR) act to inhibit norepinephrine release in cardiac and other presynaptic nerves. We have recently shown that a genetic variant in the ␣2CAR coding region (Del322-325), which renders the receptor partially uncoupled from G i, is a risk factor for heart failure. However, variability of heart failure phenotypes and a dominance of Del322-325 in those of African descent led us to hypothesize that other regions of this gene have functional polymorphisms. In a multiethnic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…This study has limitations. First, recent work shows substantial divergence between certain a 2C haplotypes and a partitioning of the a 2C Del322-325 polymorphism into multiple haplotypes (Small et al, 2004). In addition, it was shown that these haplotypes influence cellular expression of the a 2C -AR transcript and protein.…”
Section: Discussionmentioning
confidence: 99%
“…This study has limitations. First, recent work shows substantial divergence between certain a 2C haplotypes and a partitioning of the a 2C Del322-325 polymorphism into multiple haplotypes (Small et al, 2004). In addition, it was shown that these haplotypes influence cellular expression of the a 2C -AR transcript and protein.…”
Section: Discussionmentioning
confidence: 99%
“…a 2A -AR Asn251Lys polymorphism was not detected. The allele frequencies of these polymorphisms were different for different ethnic backgrounds as shown in previous reports (Shibata et al 1996;Small et al 2004Small et al , 2006Xie et al 1999). Table 2 shows the clinical characteristics for each a-AR polymorphism according to the genotype.…”
Section: Resultsmentioning
confidence: 82%
“…Finally, the findings in the present study should be considered as preliminary because several other polymorphisms have been identified in each a-AR (Buzas et al 2004;Gu et al 2006;Small et al 2004Small et al , 2006, and therefore, the haplotype or gene-gene interactions may modulate the association of a-AR polymorphisms with cardiac autonomic function. Analyses stratified by the haplotypes or combined genotypes for the a-AR polymorphisms are required in a large number of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations